PENDIDIKAN GEOLOGI MILITER DI INDONESIA, SUATU TANTANGAN BAGI PUSDIKLAT GEOLOGI DAN PERGURUAN TINGGI PENYELENGGARA PENDIDIKAN SAINS KEBUMIAN - -, Zufialdi Zakaria (Fakultas Teknik Geologi Universitas Padjadjaran, 2010)
Geology plays a role in various fields. In the field of military and national defense, geological branch that play a role is military geology. In Indonesia, there are no special units of military geology that handling of military geology. Military geology education was also not in the curriculum of the University of geoscience education providers. Geological training and education center is also not have modules and syllabus for military geology . These conditions is a challenge to provide military-geology education for personnel of military of Indonesian National Army , or to the geologists who are interested in working in the military